Construction of histidine-containing hydrocarbon stapled cell penetrating peptides for in vitro and in vivo delivery of siRNAs. Issue 15 (3rd April 2018) - Hyun, Soonsil; Choi, Yoonhwa; Lee, Ha Neul; Lee, Changki; Oh, Donghoon; Lee, Dong-Ki; Lee, Changjin; Lee, Yan; Yu, Jaehoon
Abstract : A hydrocarbon stapled peptide, LKH-stEK, promotes delivery of nanomolar siRNAs leading to efficient gene silencing in mouse skin. Abstract : A hydrocarbon stapled peptide based strategy was used to develop an optimized cell penetrating peptide for siRNA delivery. Various stapled peptides, having amphipathic Leu- and Lys-rich regions, were prepared and their cell penetrating potentials were evaluated. One peptide, stEK, was found to have high cell penetration and siRNA delivery abilities at low nanomolar concentrations. In order to improve its ability to promote gene silencing, stEK was modified by replacing several Lys residues with His moieties. The modified peptide, LKH-stEK, was found to facilitate endosomal escape and to display >90% knock-down with 50 nM of a siRNA targeting cyclophilin B in HeLa cells. The results of an in vivo animal wound healing model study demonstrate that LKH-stEK promotes delivery of an siRNA, which targets the connective tissue growth factor, and that this process leads to efficient gene silencing by the siRNA at a nanomolar level in mouse skin.